Cystic Meningiomas: A Radiological and Histological Study and Pre Operative Diagnostic Errors - Chandra, Jaideep; KC, Raj Kumar (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Meningiomas are solid neoplasms, cysts are extremely rare, diagnostically elusive, and behave differently. Therefore, a study was initiated comparing our cases with various series. This is the second largest series so far reported. We tried to hypothesize how to eliminate diagnostic errors in this study, while few interesting points were discovered. MATERIAL AND METHODS: All meningiomas operated in the last seventeen years were reviewed. It was a retrospective study. Diagnostic errors, clinical behaviour and histopathology were reviewed. Planning of surgery and prognostication demands that the diagnosis be established pre-operatively and since these tumours may mimic other brain tumour types on radiology , factors that may lead to better diagnostic accuracy were tried to be established. Categorization of the tumours with different cyst types according to various classifications was done. The follow up period was two months to ten years. RESULTS: Out of 530 meningiomas, we found 20 with cystic changes.. There mean age was 47.5 years. The commonest symptoms were raised intra cranial pressure, hemiparesis, memory loss, behavioral changes, vision loss, papilloedem and cranial nerve palsies. The most common histological variety was meningothelial meningioma. The incidence of high grade or malignant tumors was 30 %. Based on radiology, the highest diagnostic accuracy was achieved in 62.5% cases only. CONCLUSION: Cystic meningiomas continue to pose diagnostic challenges. Multi-planar contrast magnetic resonance imaging (MRI) will help in establishing accurate diagnosis, it reveals cysts missed on computed tomography (CT) scans. This would lead to accurate prognostication and better surgical planning with the aim of preventing recurrences.